2019
DOI: 10.3390/ijms20215439
|View full text |Cite
|
Sign up to set email alerts
|

Deep Eutectic Solvents as New Reaction Media to Produce Alkyl-Glycosides Using Alpha-Amylase from Thermotoga maritima

Abstract: Deep Eutectic Solvents (DES) were investigated as new reaction media for the synthesis of alkyl glycosides catalyzed by the thermostable α-amylase from Thermotoga maritima Amy A. The enzyme was almost completely deactivated when assayed in a series of pure DES, but as cosolvents, DES containing alcohols, sugars, and amides as hydrogen-bond donors (HBD) performed best. A choline chloride:urea based DES was further characterized for the alcoholysis reaction using methanol as a nucleophile. As a cosolvent, this D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
14
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 38 publications
0
14
0
Order By: Relevance
“…Circular dichroism measurements of Amy A showed that large conformational changes were observed above 60 • C, changes not observed in aqueous medium. The authors claim that this is the first report on the effect of DES and temperature on an enzyme, to establish the temperature limit for a thermostable enzyme in DES [10].…”
mentioning
confidence: 89%
See 1 more Smart Citation
“…Circular dichroism measurements of Amy A showed that large conformational changes were observed above 60 • C, changes not observed in aqueous medium. The authors claim that this is the first report on the effect of DES and temperature on an enzyme, to establish the temperature limit for a thermostable enzyme in DES [10].…”
mentioning
confidence: 89%
“…The use of deep eutectic solvents (DES) for the synthesis of alkyl glycosides catalyzed by the thermostable α-amylase from Thermotoga maritima Amy A was investigated by Miranda-Molina et al [10]. While DES containing alcohols, sugars, and amides as hydrogen-bond donors (HBD) as cosolvents performed best, pure DES almost completely deactivated the enzyme.…”
mentioning
confidence: 99%
“…The enzyme was almost completely deactivated when assayed in a series of pure DES, but as cosolvents, DES containing alcohols, sugars, and amides as hydrogen‐bond donors (HBD) performed best. [146] …”
Section: Organic Synthesis In Dessmentioning
confidence: 99%
“…The enzyme was almost completely deactivated when assayed in a series of pure DES, but as cosolvents, DES containing alcohols, sugars, and amides as hydrogen-bond donors (HBD) performed best. [146] 6.12. Peptide Synthesis DESs have proved to be a good alternative to traditional organic solvents and in many biocatalytic processes, [147] including enzymatic peptide synthesis.…”
Section: Glycosylationsmentioning
confidence: 99%
“…In that report the authors concluded that the moderate increase in Y (10%) justifies the use of an ionic liquid in terms of practical considerations (productivity and cost). Similarly, in the synthesis of alkyl-glycoside with the α-amylase from Thermotoga maritima the use of deep eutectic solvents (DES) provoked a reduction in enzyme stability and a decrease in enzyme activity, but favored transglycosylation (alcoholysis) over hydrolysis at concentration lower than 10% v/v (Miranda-Molina et al, 2019). In the synthesis of hexyl-β-galactoside with A. oryzae β-galactosidase (Vera et al, 2017a), the addition of 30% (v/v) acetone produced a significant increase in Y, mainly because of a decrease in secondary hydrolysis.…”
Section: Synthesis Of Butyl-β-galactoside In a Ternary Systemmentioning
confidence: 99%